2015
DOI: 10.1371/journal.pone.0121716
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Bacterial Communities of Eggshells and Antimicrobial Activities in Eggs during Incubation in a Ground-Nesting Passerine

Abstract: Microbial invasion of egg contents is a cause of embryonic death. To counter infection risks, the embryo is protected physically by the eggshell and chemically by antimicrobial proteins. If microbial pressure drives embryo mortality, then females may have evolved, through natural selection, to adapt their immune investment into eggs. Although frequently hypothesized, this match between immune allocation and microorganisms has not been explored yet. To examine if correlations between microbes on eggs and immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 71 publications
(107 reference statements)
3
32
0
Order By: Relevance
“…Changes in bacterial abundances between second laid eggs (<12 h post laying) and first laid eggs (24-36 h post laying), as a means of taxon-specific growth or thriving survivors, revealed that proliferating taxa on eggshells were not indicative for maternal cloacal microbiomes but for soil communities, and occasionally for nest material, feather and skin communities. The minimal success of gut symbionts on eggshells adds to the current understanding of egg microbiome dynamics: incubation induces an increase of bacterial abundance but a decrease of diversity of eggshell communities [29,30,35,64] enhancing egg viability through reduction of the probability of trans-shell infection [25,28]. Shawkey et al [65] showed that mainly potential pathogenic bacteria were inhibited by incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in bacterial abundances between second laid eggs (<12 h post laying) and first laid eggs (24-36 h post laying), as a means of taxon-specific growth or thriving survivors, revealed that proliferating taxa on eggshells were not indicative for maternal cloacal microbiomes but for soil communities, and occasionally for nest material, feather and skin communities. The minimal success of gut symbionts on eggshells adds to the current understanding of egg microbiome dynamics: incubation induces an increase of bacterial abundance but a decrease of diversity of eggshell communities [29,30,35,64] enhancing egg viability through reduction of the probability of trans-shell infection [25,28]. Shawkey et al [65] showed that mainly potential pathogenic bacteria were inhibited by incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Without handling eggs, we marked each first laid egg with a small dot using a water-resistant marker at the blunt end to distinguish it from second eggs. We collected both eggs when the second egg had been laid (first eggs within 36 h and second eggs within 12 h post laying), minimising egg age and incubation effects [35]. We aseptically stored eggs individually in sterile plastic bags (Whirl-Pak ® , Nasco, Fort Atkinson, WI, USA), and replaced them by ethanolsterilised homemade self-hardening clay eggs to encourage clutch completion.…”
Section: Study Species and Sample Collectionmentioning
confidence: 99%
“…Among them, variation in the eggshell microstructure (D'Alba et al, 2014;Grellet-Tinner et al, 2017), eggshell pigmentation (Ishikawa et al, 2010), deposition of egg white antimicrobial proteins (AMPs) into the eggshell membranes and cuticle (Bain et al, 2013;Gautron et al, 2011;Wellman-Labadie et al, 2008a), and cuticle nanostructuring (D'Alba et al, 2016(D'Alba et al, , 2017 have been documented to significantly reduce the eggshell microbial load. Among behavioural mechanisms, partial and full incubation of a clutch have been shown to significantly reduce the abundance (Bollinger et al, 2018;Cook et al, 2005a;D'Alba et al, 2010a;Ruiz-De-Castaneda et al, 2011 but also the diversity and community structure of the eggshell microbiota (Grizard et al, 2014(Grizard et al, , 2015Lee et al, 2014). In contrast, defence mechanisms in species of the family Megapodiidae, which do not incubate their clutches, lie in the covering of the eggshells with an inorganic layer of nanometer-scale spheres of hydroxyapatite, making the eggshells super-hydrophobic and preventing attachment by bacteria (D'Alba et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While lysozyme has significant bactericidal activity against Gram-positive as well as Gram-negative bacteria (Ibrahim et al, 2001;Wellman-Labadie et al, 2008a), ovotransferrin is primarily bacteriostatic via its iron-binding potential, forming an iron-deficient environment, inhibiting the growth of many microorganisms (Wu and Acero-Lopez, 2012). However, the concentration and antimicrobial activity of egg white lysozyme and ovotransferrin have been documented to vary during the incubation cycle (Fang et al, 2012a, b;Qiu et al, 2012;Grizard et al, 2015;Liu et al, 2015). These changes in AMP activity are considered to be linked with alterations in egg white pH (Smolelis and Hartsell, 1952;Ibrahim et al, 1994;Halbrooks et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Parental and breeding activity, as well as nest material and ectoparasites, determine bacterial environment of nesting cavities and of eggshells (González-Braojos et al 2012, Peralta-Sánchez et al 2012, Grizard et al 2015, Tomás et al 2018. These bacteria can have positive, negative or no effects on the offspring (Singleton and Harper 1996, Moreno et al 2003, González-Braojos et al 2012, Soler et al 2017, Devaynes et al 2018.…”
Section: Introductionmentioning
confidence: 99%